The Problems in Translating A Short Story "Arinillah" by Taufik Hakim in Terms of Grammar - Lutfhian, Muhammad Daud; Rauf, Shofwan Anwar Abdul; Kholis, Muhammad Nur (Asalibuna, 2021)
The problem in this study is the problem of grammar contained in the translation of a collection of short stories Arinillah by Taufik Hakim. This study aims to determine the number of grammatical issues and the types of grammatical problems in the translated text of Arinillah's short story with the theme of love. This research is included in library research with the primary data in the form of words, sentences, and expressions contained in Arinillah's short story collection. The data obtained were then categorized according to their type and then analyzed. From the study results, it was found that there were grammatical problems at the level of phrases and sentences contained in four short stories with the theme of love. This study resulted in 63 grammatical problems in translating a collection of short stories by Taufiq Al-Hakim arinillah. The issues can be classified into several types: tarkib washfi, tarkib idhafi, atahf mathuf, taukid, simple sentences, complete sentences, and complex sentences.